Activation of epigenetic regulator KDM6B by Salmonella Typhimurium enables chronic infections. (1st January 2021) - Rana, Sarika; Maurya, Sonalika; Mohapatra, Gayatree; Singh, Savita; Babar, Rohan; Chandrasekhar, Hridya; Chamoli, Garima; Rathore, Deepak; Kshetrapal, Pallavi; Srikanth, C. V.
ABSTRACT: Non-typhoidal Salmonella (NTS) infections result in self limiting gastroenteritis except in rare cases wherein manifestations of chronic infections can occur. Strategies employed by Salmonella to thrive in hostile environments of host during chronic infections are complex and multifaceted. In chronic state, a coordinated action of bacterial effectors allows reprogramming of macrophages to M2 subtype and thereby creating a permissible replicative niche. The mechanistic details of these processes are not fully known. In the current study we identified, histone H3-lysine 27 trimethylation (H3K27me3)-specific demethylase, KDM6B to be upregulated in both cell culture and in murine model of Salmonella infection. KDM6B recruitment upon infection exhibited an associated loss of overall H3K27me3 in host cells and was Salmonella SPI1 effectors coordinated. ChIP-qRT-PCR array analysis revealed several new gene promoter targets of KDM6B demethylase activity including PPARδ, a crucial regulator of fatty acid oxidation pathway and Salmonella- persistent infections. Furthermore, pharmacological inhibition of KDM6B demethylase activity with GSKJ4 in chronic Salmonella infection mice model led to a significant reduction in pathogen load and M2 macrophage polarization in peripheral lymphoid organs. The following work thus reveals Salmonella effector-mediated epigenetic reprogramming of macrophages responsible for its long-term survival and chronic carriage.